Benzoin thiosemicarbazone - Dinçer, M; Özdemir, N; Çukurovali, A; Yilmaz, I (Int Union Crystallography, 2005)
In the title compound, C15H15N3OS, the thiosemicarbazone moiety is planar, with a maximum deviation of 0.0369 (11) angstrom, and has an E configuration. The planar phenyl rings make dihedral angles of 26.56 (9) and 81.20 (5)degrees with the plane of the thiosemicarbazone moiety. In the molecule, there are two intramolecular interactions of types N-H center dot center dot center dot O and N-H center dot center dot center dot N. In the crystal structure, there are two intermolecular interactions of types O-H center dot center dot center dot S and N-H center dot center dot center dot S, leading to the formation of dimers.
Keywords: Crystal-Structure; Molecular-Structures; Reductase; Agents